Ayat-Ayat Al-Qur’an Tentang Motivasi Kerja Dalam Islam - Isra Adawiyah Siregar, Mukthi Halwi (ALACRITY : Journal of Education, 2021)
This paper explains work motivation in Islam from the perspective of the verses of the Koran. Interpretation of Al-Qur'an verses related to work motivation in Islam and suggest a correlation between Al-Qur'an verses and work motivation theory. Motivation is a power or desire that comes from the human conscience to do a certain action. Meanwhile, work motivation in Islam is to earn a living which is part of worship, which is of course not only for pursuing a hedonistic life, not also for status, let alone pursuing wealth by all means. Thus, work motivation in Islam is not only fulfilling a living but as an obligation to worship Allah after other fardhu worship. Because, the glory of a man depends on what he does. With that, a practice or work that brings someone closer to Allah is very important and deserves attention. Practices or jobs like this apart from obtaining the blessings and pleasures of the world, there is also something more important, which is a way or ticket in determining the stage of one's life in the hereafter, whether it is in the heavenly expert class or vice versa. Through this article, the author tries to provide an explanation and express the verses related to work motivation in Islam.